Synergistic Effect of Linezolid, Tigecycline, and Vancomycin on Staphylococcus Aureus Isolated From Iraqi Patients with Diabetic Foot Ulcers - Al-hamedawy, Hayder H. Hasan; Mahmoud, Suhad Saad (Iraqi Journal of Science, 2019)
Ninety nine swabs were collected from patients with diabetic foot ulcers (DFU), all swabs were cultured on different selective media for screening, 46 isolates confirmed as S. aureus by API staph. The results of antibiotic susceptibility test revealed that all isolates were resistant to metronidazole, 34 isolates were resistant to cefoxitin, ceftriaxone, and meropenim, 23 isolates were resistant to ciprofloxacin and norfloxacin, 17 and 16 isolates were resistant to tetracycline and trimethoprim, respectively; while all isolates were sensitive to tigecycline. The results of minimum inhibitory concentration (MIC) that carried out by using vancomycin, tigecycline and linezolid for 8 isolates, MIC results were1-2 µg /ml, 0.25-0.5 µg /ml, 4 µg /ml, respectively; 4 isolates were selected according to their aggressive antibiotic resistance to test the antibiotics` combinations effects, the combination of vancomycin/ tigecycline presented promising results against S. aureus infections at low concentrations.